2006
DOI: 10.1007/s11914-996-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and pathophysiology of osteoporosis in men

Abstract: Osteoporosis in men is an unrecognized but growing problem as the number of men who live to old age increases. The 10-year fracture risk at age 50 quadruples by age 80, and in general the incidence rate of osteoporotic fracture in men is about half that of women. Of note, the mortality and morbidity after hip fracture are much greater in men. There are many men whose osteoporosis is the result of specific causes such as oral glucocorticoid therapy, hypogonadism, or androgen withdrawal therapy for prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…These values are higher than those reported previously (Brzozowska et al, 2002) and might indicate a better prevention of osteoporosis among women in Switzerland. Still, although male gender and increased body mass index might be protective towards osteoporosis (Felson et al, 1993), the low prevalence of calcium supplements (with or without vitamin D) in men raises some concern, as it has been shown that dietary calcium intake among elderly is below the recommended levels (Gennari, 2001;Marshall et al, 2001;Sharkey et al, 2002;Dumartheray et al, 2006) and that mortality and morbidity after hip fracture are much greater in men (Adler, 2006). Supplemental iron is usually prescribed for anaemia, which is more frequent among premenopausal women (Hercberg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These values are higher than those reported previously (Brzozowska et al, 2002) and might indicate a better prevention of osteoporosis among women in Switzerland. Still, although male gender and increased body mass index might be protective towards osteoporosis (Felson et al, 1993), the low prevalence of calcium supplements (with or without vitamin D) in men raises some concern, as it has been shown that dietary calcium intake among elderly is below the recommended levels (Gennari, 2001;Marshall et al, 2001;Sharkey et al, 2002;Dumartheray et al, 2006) and that mortality and morbidity after hip fracture are much greater in men (Adler, 2006). Supplemental iron is usually prescribed for anaemia, which is more frequent among premenopausal women (Hercberg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…59 The skeletal role of androgens upon cancellous bone is largely mediated by local aromatization into estrogens. 60 Androgen deficiency in men induces cancellous bone loss similar to estrogen deficiency in postmenopausal women. 60 In elderly men with hypogonadism, the resultant testosterone deficiency contributes to osteoporosis.…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…60 Androgen deficiency in men induces cancellous bone loss similar to estrogen deficiency in postmenopausal women. 60 In elderly men with hypogonadism, the resultant testosterone deficiency contributes to osteoporosis. Although treatment of frank androgen deficiency with androgen replacement therapy is beneficial for bone, 61-63 the effect of androgen replacement on fracture incidence remains unknown.…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…In addition, testosterone levels naturally decrease with age, and men being eugonadal in early adulthood can develop androgen deficiency in more advanced age (4). Men with severe hypogonadism face the risk of developing osteoporosis, depression, and disturbed metabolism that might lead to metabolic syndrome and type 2 diabetes, as well as cardiovascular diseases (5)(6)(7). In some studies, these conditions were shown to be ameliorated by testosterone replacement (8,9).…”
mentioning
confidence: 99%